1988
DOI: 10.1071/wr9880435
|View full text |Cite
|
Sign up to set email alerts
|

Fox control and rock-wallaby population dynamics

Abstract: The population dynamics of five remnant rock-wallaby populations (Petrogale lateralis) persisting on granite outcrops in the central wheatbelt region of Western Australia were monitored over a six year period. From 1979 to 1982 all populations remained relatively static or declined for unknown reasons, but circumstantial evidence implicated fox predation. A fox control program was implemented in 1982 on two outcrops and was maintained for four years with the result that the two resident rock-wallaby population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(155 citation statements)
references
References 5 publications
8
147
0
Order By: Relevance
“…Studies on the impacts of introduced predators on Australia's native wildlife have focused primarily on direct predatory impacts (e.g. Kinnear, Onus & Bromilow, 1988;Priddel, 1989 ;Kinnear, Onus & Sumner, 1998 ;Mahon, 1999;Kinnear, Sumner & Onus, 2002). However, several authors have suggested that introduced predators may also impact upon native species through competition for resources such as food, territories and den sites (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the impacts of introduced predators on Australia's native wildlife have focused primarily on direct predatory impacts (e.g. Kinnear, Onus & Bromilow, 1988;Priddel, 1989 ;Kinnear, Onus & Sumner, 1998 ;Mahon, 1999;Kinnear, Sumner & Onus, 2002). However, several authors have suggested that introduced predators may also impact upon native species through competition for resources such as food, territories and den sites (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Only two individuals were caught, but this experience led us to suspend our trapping endeavours pending the subsequent development of the original Mark 1 Bromilow soft trap (Kinnear et al 1988) (Fig. 1a).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…The original Mark I chamber consisted of netting that visually exposed the lure (apple) to interested rock-wallabies (Kinnear et al 1988). The rock-wallabies soon learned to attack the lure from the outside and, in doing so, they frequently triggered the trap.…”
Section: The Mark I Capture Chambermentioning
confidence: 99%
See 2 more Smart Citations